Study on the effect of front retaining walls on the thermal structure and outflow temperature of reservoirs. - Xiaoqian Yang; Youcai Tuo; Yanjing Yang; Xin Wang; Yun Deng; Haoyu Wang (PLoS ONE)
The front retaining wall (FRW) is an effective facility of selective withdrawal. Previous research has not estimated the effect of FRWs on the thermal regimes of reservoirs and outflow temperature, which are crucial to reservoir ecology. For this purpose, taking the Dongqing Reservoir as a case study, a two-dimensional hydrodynamic CE-QUAL-W2 model was configured for the typical channel-type reservoir in the southwestern Guizhou Province, to better understand the influence of FRWs on the thermal structure and outflow temperature. The simulated data from January to September 2017 showed that FRWs can change the vertical temperature distribution during the stratification period, accelerate the upper warmer water release and thus decrease the strength of thermal stratification. The stratification structure changed from a single thermocline to double thermoclines in August. An FRW resulted in an average 11.8 m increase in the thickness of the hypolimnion and a 1.2°C decrease in the thickness of the thermocline layer. An FRW increased the outflow temperature by 0.4°C and raised the withdrawal elevation by 16 m on average. The longitudinal velocity increased compared with the non-FRW condition, while the maximum velocity position moved up. In addition, FRWs can continuously obtain surface warmer water without manual operation and have low investment and good construction conditions. This study can provide an available selective withdrawal idea for reservoirs with similar hydraulic conditions.